Hydrographic changes in the Lincoln Sea in the Arctic Ocean with focus on an upper ocean freshwater anomaly between 2007 and 2010. Issue 9 (20th September 2013) - de, L.; Steele, M.; Hansen, E.; Morison, J.; Polyakov, I.; Olsen, S. M.; Melling, H.; McLaughlin, F. A.; Kwok, R.; Smethie, W. M.; Schlosser, P.
<x xml:space="preserve">Abstract</x> [1] Hydrographic data from the Arctic Ocean show that freshwater content in the Lincoln Sea, north of Greenland, increased significantly from 2007 to 2010, slightly lagging changes in the eastern and central Arctic. The anomaly was primarily caused by a decrease in the upper ocean salinity. In 2011 upper ocean salinities in the Lincoln Sea returned to values similar to those prior to 2007. Throughout 2008–2010, the freshest surface waters in the western Lincoln Sea show water mass properties similar to fresh Canada Basin waters north of the Canadian Arctic Archipelago. In the northeastern Lincoln Sea fresh surface waters showed a strong link with those observed in the Makarov Basin near the North Pole. The freshening in the Lincoln Sea was associated with a return of a subsurface Pacific Water temperature signal although this was not as strong as observed in the early 1990s. Comparison of repeat stations from the 2000s with the data from the 1990s at <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t8w4j0n" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />65°W</alternatives> showed an increase of the Atlantic temperature maximum which was associated with the arrival of warmer Atlantic water from the Eurasian Basin. Satellite‐derived dynamic ocean topography of winter 2009 showed a ridge extending parallel to the Canadian Archipelago shelf as far as the Lincoln Sea, causing a strong flow toward Nares Strait and likely Fram Strait. The total volume of anomalous freshwater observed in the Lincoln Sea and exported by 2011 was close to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t8w4j5d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1100±250km3</alternatives>, approximately 13% of the total estimated FW increase in the Arctic in 2008.